Faktor – Faktor Yang Mempengaruhi Efektivitas Sistem Pengendalian Intern (Studi Pada OPD Pemerintah Provinsi Sumatera Selatan) - Juliana, Mery; Periansya; Satriawan, Indra (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine the effect of leadership style, accounting information systems and audit quality on the effectiveness of the internal control system. The type of data used in this study is primary data. The data in this study were obtained from the collection of questionnaires distributed. The population in this study were 39 Regional Apparatus Organizations (OPD) of the South Sumatra Provincial Government with a sample of 39 Regional Apparatus Organizations (OPD) of the South Sumatra Provincial Government and the sample selection method using purposive sampling. The statistical method in testing the hypothesis in this study is multiple linear regression analysis. The results of this study state that: (1) leadership style, accounting information system and audit quality partially and significantly affect the effectiveness of the internal control system and (2) leadership style, accounting information system and audit quality simultaneously and significantly affect the effectiveness of the internal control system in the Regional Apparatus Organization (OPD) of the South Sumatra Provincial Government.